Implementation of Contextual Teaching and Learning (CTL) To Improve Student Learning Outcomes In Subject Study Forces Affect The Movement of Objects In Class IV SDN II Ponrewaru - Marwati; Sundari Hamid (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2023)
Based on the researcher's experience while teaching the style material influencing the motion of objects in class IV SDN II Ponrewaru, Kolaka Regency and the results of interviews with the class IV teacher for his experience teaching Natural Sciences, it does not activate students directly in the learning process, it does not give students the opportunity to construct knowledge that is has by connecting it with phenomena that exist in the environment around students. Based on this, the formulation of the problem in this study is whether the application of Contextual Teaching and Learning (CTL) can improve learning outcomes of the subject matter gayaaffecting the motion of objects in class IV SDN II Ponrewaru, Kolaka Regency. This study uses a qualitative approach to the type of action research. Actions in this study consisted of two cycles. Each cycle goes through four stages, namely planning, implementing, observing, and reflecting. From the formulation of the problem, data presentation and discussion, it is concluded that learning through the application of Contextual Teaching and Learning (CTL) to improve student learning outcomes on the subject of styles influencing motion of objects in class IV DSN II Ponrewaru, Kolaka Regency, this learning is carried out in five stages, namely the initial stage , the core stage, and the final stage. activities in the early stages include: (1) explaining the learning objectives (2) explaining the tools needed and motivating students to be involved in problem solving activities. while the core activities consist of (1) managing students' initial knowledge to the problem (2) guiding the investigation and the group. While the final activity includes (1) reflecting on the problem solving process (2) providing an evaluation. Based on the evaluation of the process and the evaluation of the results in each study, the student learning outcomes in the subject of language gayainfluencing the motion of objects at SDN II Ponrewari increased by using the Contextual Teaching and Learning approach.